ANALYSIS OF BEEF CATTLE MARKETING CHANNEL EFFICIENCY IN LAMPOKO VILLAGE, BARRU REGENCY - Mihrani; Abdurrahman Faris Wahid; Subhan Effendi (ITScience (Information Technology and Science), 2022)
The purpose of this study was to analyze marketing channels, marketing margins, marketing farmer's share rate, and marketing efficiency of beef cattle in Lampoko Village, Barru Regency. The sample of this study was 12 breeders, 5 traders and 3 consumers. The data collection method is carried out by interviews (questionnaires) and literature studies. The method of sampling farmers is by purposive sampling method while the sample of traders and consumers uses snowball sampling method. The strategy that must be done to deal with competitors is to increase promotion and maintain product quality. This aims to increase consumer attractiveness, expand market share and reduce the risk of similar competing products. The results showed that there were 3 channels of beef cattle marketing channels in Lampoko Village, namely; Farmers Collecting Traders Consumer Wholesalers, Farmers Collecting Traders Consumers / RPH, and Farmers Wholesalers Consumers. The highest marketing margin is channel I and III of Rp. 3,000,000 while channel II is Rp. 1,000,000. The highest Farmer's Share rate on channel II is 89%, channel I and III is 77%. The most efficient levels of marketing efficiency are channel II with 25%, channel III with 50% and channel I with 70%